“Il ruolo delle università pontificie nell’evangelizzazione della cultura alla luce della Costituzione Veritatis gaudium” - Zani, Mons. Angelo Vincenzo (Alpha Omega, 2020)
Summary: Following the thought of Pope Francis in the Constitution, Veritatis gaudium, the author offers three points of fundamental importance for consideration. 1. To provide a synthetic summary of those elements which have accompanied the changes in ecclesiastical studies from the Council up to our own days, in relation to the evangelisation of culture. 2. To recover clearly the paradigm which underlies the thought of Pope Francis and which we find especially in the exhortation Evangelii gaudium, as indeed in his teachings and in his gestures as a whole. 3. To show how the relationship between the structuring of ecclesiastical studies and the evangelisation of culture should be expressed in some of the choices which are to be made in the course of time. The framework which emerges from these emphases is that of a “Catholic” thought, which understands the Church and life as a complexio oppositorum, as an agonising struggle to pacify conflicts, to prevent these polarities from dissolving themselves manichaeistically into contradictions. This is the framework which constantly accompanies the magisterium of the Pope and it is one which has decisive relevance for the relationship between evangelisation and culture. The author develops the consequences of this approach for catholic education, especially in the pontifical universities. Key words: evangelisation, culture, ecclesiastical studies, Veritatis gaudium, Evangelii gaudium, (Pope) Francis, Catholic education, university, mission, a trans-disciplinary approach, integral formation. Parole chiave: Evangelizzazione, cultura, studi ecclesiastici, Veritatis gaudium, Evangelii gaudium, (Papa) Francesco, educazione cattolica, università, missione, transdisciplinarietà, formazione integrale.